Oswell, John (London, 2011)
2011 "Oswell, John", 2011, HistoryTalk John left school at fifteen in 1962. His first job was an apprentice printer (compositor). He moved to work as a lathe operator that produced gold leaf. He then worked in the motor transportation, delivering photographic equipment to studios across London, which was the new London scene of the 1960s. He worked from 7am to 7pm, a 60- hour week. He then in a number of driving jobs, with progressively heavier vehicles and then finally joined Esso Petroleum in 1973 and worked for them for some 24 years. He describes how he loved his job, with good money and pension provision. He notes the background of power cuts under Heath's government and the 3- day week. He was one of new generation of tanker drivers as North Sea oil being discovered in 1973. He describes the driving job and the pride that drivers retain despite huge changes in the industry. He left the industry in 1995.